Detection by broad-range real-time PCR assay of Chlamydia species infecting human and animals. Issue 11 (9th August 2006) - Goldschmidt, P; Rostane, H; Sow, M; Goépogui, A; Batellier, L; Chaumeil, C
Abstract : Background: Tests available for molecular diagnosis of chlamydial infections detect Chlamydia trachomatis, but do not find other Chlamydia species associated with genital, ophthalmic, cardiovascular, respiratory or neurological diseases. The routine detection of all Chlamydia species would improve the prognosis of infected people and guide therapeutic choices. Aim: To design and validate a sensitive, specific, reproducible, inexpensive and easy-to-perform assay to quantify most Chlamydia species. Methods: Primers and probe were selected using the gene coding for the 16S rRNA. The detection limits were assessed for suspensions of Chlamydia trachomatis, Chlamydia psittaci and Chlamydia pneumoniae . The performance of this test was compared with that of two commercial kits (Amplicor-Roche and Artus) on 100 samples obtained from children with trachoma. Results: The detection capacities for Chlamydia trachomatis of the broad-range real-time polymerase chain reaction (PCR) were similar or slightly better than those obtained with commercial kits (0.2 copies of DNA/μl). Only the broad-range PCR identified specimens containing Chlamydia psittaci and Chlamydia pneumoniae . The commercial kits and the broad-range assay detected Chlamydia species in 5% and in 11%, respectively, of samples from children with trachoma. Conclusions: This new real-time PCR offers a sensitive, reproducible assay that produces results in <3 h. With panels of quantified Chlamydia species, this real-time PCR can be run with all real-time PCR equipment. Larger trials are needed to confirm the utility of this test in diagnosis and for therapeutic follow-up.